Associations between psychometrically assessed life history strategy and daily behavior: data from the Electronically Activated Recorder (EAR) - Manson, Joseph H. (PeerJ, 2018)
Life history theory has generated cogent, well-supported hypotheses about individual differences in human biodemographic traits (e.g., age at sexual maturity) and psychometric traits (e.g., conscientiousness), but little is known about how variation in life history strategy (LHS) is manifest in quotidian human behavior. Here I test predicted associations between the self-report Arizona Life History Battery and frequencies of 12 behaviors observed over 72 h in 91 US college students using the Electronically Activated Recorder (EAR), a method of gathering periodic brief audio recordings as participants go about their daily lives. Bayesian multi-level aggregated binomial regression analysis found no strong associations between ALHB scores and behavior frequencies. One behavior, presence at amusement venues (bars, concerts, sports events) was weakly positively associated with ALHB-assessed slow LHS, contrary to prediction. These results may represent a challenge to the ALHB’s validity. However, it remains possible that situational influences on behavior, which were not measured in the present study, moderate the relationships between psychometrically-assessed LHS and quotidian behavior.
Keywords: Life history strategy; Electronically activated recorder; Arizona life history battery